On-chip nano-localization via transverse kerker scattering - Bag, Ankan; Neugebauer, Martin; Mick, Uwe; Christiansen, Silke; Schulz, Sebastian A.; Banzer, Peter (Optics InfoBase Conference Papers, 2020)
Here we present a transverse Kerker scattering based sub-wavelength localization technique transferred to a chip-scale all-optical displacement sensing device, which could act as a metrological instrument in modern lithography and microscopy, or monitor system drifts.
CRIS-Team Scopus Importer:2023-03-07